A brief review on factors that influencing the removal efficiency of stormwater interceptor system - Chow M.F.; Aaba A. (American Institute of Physics Inc., 2023)
Many storm water managements attempted to remove the particulate sediments before the runoff reaches the receiving water body. It is vital for the sedimentation tank to be operative at its complete potential. It seems theoretically comprehensive process, yet complicated to apply. Hence, a proper consideration of the tank behaviour is crucial for designing and operating process. Based on the review of previous studies, it was found that particle size distribution and solids loading rates, tank type, flow pattern and baffle are the factors that affecting the sedimentation tank performance. 2021 American Institute of Physics Inc.. All rights reserved.